Occult hepatitis B in patients with cancer during immunotherapy with or without chemotherapy: A real-life retrospective single-center cohort study - Angioletta Lasagna; Giuseppe Albi; Renato Maserati; Andrea Zuccarini; Mattia Quaccini; Fausto Baldanti; Fausto Baldanti; Paolo Sacchi; Raffaele Bruno; Raffaele Bruno; Paolo Pedrazzoli; Paolo Pedrazzoli (Frontiers in Oncology, 2023)
IntroductionFew data about the safety of immune checkpoint inhibitors (ICIs) in the patients with solid tumor with Occult Hepatitis B Virus (OBI) are available. According to the Taormina Workshop on Occult HBV Infection Faculty Members we defined as potential-OBI (pOBI) the HBV DNA negativity with anti-hepatitis B core antibody (anti-HBc) positivity (pOBI seropositive), and the patients with HBsAg–negative and anti-HBc–negative and Hepatitis B surface antibody (anti-HBs)–negative are defined pOBI seronegative. The aim of this study is to investigate the prevalence of OBI in patients with solid tumors undergoing ICIs with or without chemotherapy and the incidence of reactivation (HBVr).MethodsWe retrospectively enrolled all HBsAg negative subjects who had received ICIs for at least three months. HBsAg and HBV DNA levels were repeated every 3 months until the end of the study and/or in case of ALT alterations. A univariate analysis was conducted in order to study for each variable available its ability to distinguish a potential OBI seropositive patient from a seronegative one.Results150 patients in our Oncology Unit were eligible. One hundred and seventeen patients (78%) received ICI as monotherapy, whereas 33 patients (22%) were treated with chemo-immunotherapy. The mainly used drugs for the ICI monotherapy were Pembrolizumab (47%), Nivolumab (33%) and Atezolizumab (11%). The prevalence of pOBI seropositive patients was 25.3%. We did not observe alterations of liver biochemistry nor HBVr.DiscussionThis study highlights that about a quarter of our population had a potential occult hepatitis B. Immunotherapy might be considered as low risk of reactivation, regardless of the potential presence of episomal covalently closed circular DNA (cccDNA) in the liver, but the correct management still represents a challenge for oncologists and hepatologists.